Role of stainless steels in desalination (Designers' handbook series, 2020)
There are several characteristics of the family of corrosion-resistant steels known as stainless steels that make them highly desirable and eminently qualified for desalination service, not only for piping applications but for all desalting plant systems. This hand book presents applicability of stainless steels for desalination services and desalting plant systems.